Predictive Policing The Role of Crime Forecasting in Law Enforcement Operations - Perry, Walter L. (RAND Corporation, 2013)
Predictive policing is the use of analytical techniques to identify targets for police intervention with the goal of preventing crime, solving past crimes, or identifying potential offenders and victims. These tools are not a substitute for integrated approaches to policing, nor are they a crystal ball. This guide assesses some of the most promising technical tools and tactical approaches for acting on predictions in an effective way.